FISHERY AND BIOLOGY OF WHITE SARDINE, ESCUALOSA THORACATA (VALENCIENNES) AT VERSOVA, BOMBAY - RAJE, S. G.; DESHMUKH, V. D.; THAKURDAS, THAKURDAS (Journal of Indian Fisheries Association, 2015)
Gill net fishery exclusively for the white sardine, Escualosa thoracata, which started in mid eighties at Versova, is described. During 1987-88 to 1991-92 period the annual average landing of the species was 202.2 tons with year to year fluctuations. The peak fishing season was during April-May. The size range of the species in the gill net was 41-105 mm and the von Bertalanffy growth parameters, Loo and K, estimated by the ELEFAN programme were 110 mm and 1.8 per year. The length-weight relationship was W = 0.000001508 L 3.3946 for the males and W = 0.000002561 L 3.2706 for the females. The food consisted of copepods, cladocerans and crustacean larvae. The size at maturity for the females was 82 mm and spawning took place during October Â· February period. The sex-ratio showed equal proportion except during January, July and October when females dominated in the catch.